The Concept of Sequential Multicomponent Reactions: A Short Synthesis of Thiazolo- and Oxazolo[1,4]benzodiazepine-2,5-diones - Kröger, Denis; Stalling, Timo; Martens, Jürgen (Synthesis, 2016)
A new synthetic sequence including two sequential multicomponent reactions leading to a wide range of thiazolo- and oxazolo-annulated benzodiazepinediones is described. This strategy features simple one-pot operations under mild conditions in combination with a high degree of diversity, and can be realized based on commercially available or easily accessible starting materials.
Keywords: Ugi reaction; multicomponent reactions; cyclization; heterocycles; imines; polycycles